PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 027 SINTONG KECAMATAN TANAH PUTIH - Jusnimar, Jusnimar; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated the low yields learn science students, because teachers have not applied learning models so that students become passive in the following study. The problems need a Class Action Research (PTK) with the application of Problem Based Learning. This study aims to improve learning outcomes of IPA for fourth grade students of SDN 027 Sintong by the number of students 18 people. This research is a classroom action research conducted in two cycles. Each cycle consists of 3 (three) meetings. Instruments of data collection in this study is the observation sheet teacher activities, student activities observation sheet and achievement test. From the results of this study showed that student learning has increased average student learning outcomes in basic score is 69.5 increased in the first cycle to 71.11 and increased again in the second cycle is 76.22. To complete learn the basic score is 44.44% increase in the first cycle to 66.66% increase again in the second cycle to 88.9%. It can be concluded that if implemented model of Problem Based Learning can improve IPA learning outcomes grade IV SDN 027 Sintong. Key Words: Problem Based Learning Model, Science Learning Outcomes